Cause-specific mortality after hospital discharge for suicide attempt or suicidal ideation: A cohort study in Piedmont Region, Italy. (May 2023) - Mehanović, Emina; Rosso, Gianluca; Cuomo, Gian Luca; Diecidue, Roberto; Maina, Giuseppe; Costa, Giuseppe; Vigna-Taglianti, Federica
Abstract: Background: Suicide attempters are at higher risk of death than the general population. The present study aims to investigate the excess of all-cause mortality and cause-specific mortality in a cohort of patients who have attempted suicide or had suicidal ideation compared with the general population. Method: The cohort included 826 patients residing in the Piedmont Region of Northwest Italy who were admitted to a hospital or emergency department for suicide attempts or suicidal ideation between 2010 and 2016. Mortality excesses of the study population compared to the general population were estimated by applying indirect standardization. Standardized Mortality Ratios and 95% Confidence Intervals were calculated for all-cause, and cause-specific, natural, and unnatural causes of death by gender and age. Results: During the 7 years of follow-up, 8.2% of the study sample died. The mortality of suicide attempters and ideators was significantly higher than that of the general population. Mortality was about twice than expected from natural causes, and 30 times than expected from unnatural causes. The mortality due to suicide was 85 times higher than that of the general population, with an excess of 126 times for females. The SMRs for all-cause mortality decreased with increasing age. Conclusions: Patients who access hospitals or emergency departments for suicide attempts or suicidal ideation are a frail group at high risk of dying from natural or unnatural causes. Clinicians should pay special attention to the care of these patients, and public health and prevention professionals should develop and implement appropriate interventions to timely identify individuals at higher risk for suicide attempts and suicidal ideation and provide standardized care and support services.